THE EFFECT OF WORDWALL EDUCATIONAL GAME ON STUDENTS’LEARNING INTEREST IN THE HIGH-GRADE MATHEMATICS LEARNINGSUBJECTS IN ELEMENTARY SCHOOL - Ita Rustiati Ridwan; Susilawati; Dinda Nuria Utami; Muhammad Hanif; Novita Larasati; Ananda Puti Gandoria; Muspiqotus Sadiyah; Inas Sadsabila; Putri Rahmawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Mathematics is a subject that is invariably found and taught on every level of education unit. Nevertheless, most of the students assume that mathematics is the most difficult learning subject compared to other learning subjects. This paper is intended to explain the influence that occurs on the Wordwall game on elementary students’ learning interest inmathematics and describe students' learning interest in Mathematics. The method used in the research is to use quantitative methods with experimental research in the form of pre-test and post-test. The research subjects were the fifth-grade students at SD Islam Subulussalam, SDN02 Cijoro Lebak, SDN Kampungbaru. The researchers took a total sample of 37 students using the purposive sampling technique. In terms of the statistical data analysis, the results were obtained after applying the treatment. The results, which was the sig value of 0.006<0.05, indicate that there were differences before and after applying treatment. The research results reveal that the Wordwall educational game has an effect on the fifth-grade students’ learning interest at SD Islam Subulussalam, SDN 02 Cijoro Lebak, SDN Kampungbaru on Mathematics learning subjects, especially in multiplication and division learning material. Thus, it can beconcluded that between variables Wordwall and students’ learning interest, both have an effect, provide a description regarding the conducted research, and are written clearly and completely.